Neuroprotective effects of ginsenosides Rh1 and Rg2 on neuronal cells - Jiang Zhi-Hong; Lui Cathy; Li Xiao-Fan; Ken Yung (BMC, 2011)
Abstract Background The present study investigates the effects of ginsenosides Rh1 and Rg2 against 6-hydroxydopamine (6-OHDA), a neurotoxin on SH-SY5Y cells and PC-12 cells. The effects of these two ginsenosides on neuronal differentiation are also examined. Methods LDH assay was used to measure cell viability after exposure to 6-OHDA and ginsenosides. Neuronal differentiation was evaluated by changes in cell morphology and density of neurite outgrowths. Western blotting was used to determine the ginsenosides' effects on activation of extracellular signal-regulated protein kinases (ERKs). Results Rh1 and Rg2 attenuated 6-OHDA toxicity in SH-SY5Y cells and induced neurite outgrowths in PC-12 cells. 6-OHDA-induced ERK phosphorylation was decreased by Rh1 and Rg2. 20(R)-form and 20(S)-form of the ginsenosides exerted similar effects in inducing neurite outgrowths in PC-12 cells. Conclusion The present study demonstrates neuroprotective effects of ginsenosides Rh1 and Rg2 on neuronal cell lines. These results suggest potential Chinese medicine treatment for neurodegenerative disorders (eg Parkinson's disease).